2010
DOI: 10.1590/s0034-89102010005000020
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the income inequality hypothesis and human health: a worldwide exploration

Abstract: OBJECTIVE: To analyze whether the relationship between income inequality and human health is mediated through social capital, and whether political regime determines differences in income inequality and social capital among countries. METHODS: Path analysis of cross sectional ecological data from 110 countries. Life expectancy at birth was the outcome variable, and income inequality (measured by the Gini coefficient), social capital (measured by the Corruption Perceptions Index or generalized trust), and polit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…In one of the most explored theoretical models, inequality generates social corrosion, corruption and alterations in social capital, thereby creating a hostile social environment, which produces a risk to overall health, including mental health [60]. However, these pathways have not been fully elucidated and, therefore, this constitutes a promising field of research.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the most explored theoretical models, inequality generates social corrosion, corruption and alterations in social capital, thereby creating a hostile social environment, which produces a risk to overall health, including mental health [60]. However, these pathways have not been fully elucidated and, therefore, this constitutes a promising field of research.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study suggest that income inequality has a negative effect on health and environmental quality. Idrovo et al (2010) in a cross-country study in 110 countries showed that social capital and income inequality have a direct effect on life expectancy. Elgar (2010) in a study examined the relationship between income inequality and public health in 33 countries.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Some effects of income inequality on health have been extensively explored within the "income inequality hypothesis" framework. Other macro-determinants require more empirical studies, following alternative approaches 6 .…”
Section: Introductionmentioning
confidence: 99%